2011
DOI: 10.3343/kjlm.2011.31.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tandem Mass Spectrometry for Newborn Screening of 6 Lysosomal Storage Disorders in a Korean Population

Abstract: BackgroundWe evaluated the performance of multiplex tandem mass spectrometry (MS/MS) in newborn screening for detection of 6 lysosomal storage disorders (LSDs), namely, Niemann-Pick A/B, Krabbe, Gaucher, Fabry, and Pompe diseases and Hurler syndrome.MethodsWe revised the conditions and procedures of multiplex enzyme assay for the MS/MS analysis and determined the precision of our enzyme assay and the effects of sample amounts and incubation time on the results. We also measured the degree of correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…There has also been increasing interest in NBS for LSDs, and significant progress with Pompe disease screening has been reported in Taiwan, [151][152][153] Japan, 154 and Korea. 155 Additional pilot studies in the region for other LSDs (Niemann-Pick A/B, Krabbe, Gaucher, Fabry, and Hurler syndrome) have been reported. [156][157][158][159] Other conditions for which there have been ongoing NBS pilot studies include citrin deficiency, 160 SCID, 161 Fragile-X syndrome, 162 X-ALD, 44 and Wilson's disease.…”
Section: Asia Pacificmentioning
confidence: 96%
“…There has also been increasing interest in NBS for LSDs, and significant progress with Pompe disease screening has been reported in Taiwan, [151][152][153] Japan, 154 and Korea. 155 Additional pilot studies in the region for other LSDs (Niemann-Pick A/B, Krabbe, Gaucher, Fabry, and Hurler syndrome) have been reported. [156][157][158][159] Other conditions for which there have been ongoing NBS pilot studies include citrin deficiency, 160 SCID, 161 Fragile-X syndrome, 162 X-ALD, 44 and Wilson's disease.…”
Section: Asia Pacificmentioning
confidence: 96%
“…As we found affected cases with an initial screening result close to the cutoffs for Pompe and Gaucher diseases (Table 6), we think we were at the very limit and further reduction would have resulted in missed diagnoses. Recently, Han et al (2011) reported a small-scale NBS for a Korean cohort, analyzing 211 normal newborns and 13 newborns with various LSDs to establish an NBS for LSDs in Korea; however, due to the small cohort no conclusion as to the prevalence of LSDs in Korea could be drawn. The data obtained by the newborn screening in Szeged is representative of the ethnicities found in the entire Hungarian population.…”
Section: Discussionmentioning
confidence: 99%
“…Using the MS/MS method, a Korean study also reported that the mean GAA activity of them was approximately 24 μmol/h/L [24]. Thus, higher GAA activity may be limited to Asian populations.…”
Section: Discussionmentioning
confidence: 99%